Artificial light at night affects brain plasticity and melatonin in birds - Moaraf, Stan; Vistoropsky, Yulia; Pozner, Tatyana; Heiblum, Rachel; Okuliarová, Monika; Zeman, Michal; Barnea, Anat (Neuroscience Letters, 2019)
Artificial light at night (ALAN), which disrupts the daily cycle of light, has vast biological impacts on all organisms, and is also associated with several health problems. The few existing studies on neuronal plasticity and cognitive functions in mammals indicate that a disruption of the circadian cycle impairs learning and memory and suppresses neurogenesis. However, nothing is known about the effect of ALAN on neuronal plasticity in birds. To this end, zebra finches (Taeniopygia guttata) were exposed to ecologically relevant ALAN intensities (0.5, 1.5 and 5 lx), treated with BrdU to quantify cell proliferation in their ventricular zone (VZ), and compared to controls that were kept under dark nights. We found, in our diurnal birds, that ALAN significantly increased cell proliferation in the VZ. However, neuronal densities in two brain regions decreased under ALAN, suggesting neuronal death. In addition, ALAN suppressed nocturnal melatonin production in a dose-dependent manner, and might also increase body mass. Taken together, our findings add to the notion of the deleterious effect of ALAN.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Artificial light at night (ALAN); Cell proliferation; Circadian cycle; Melatonin; Neuronal densities; Zebra finches (Taeniopygia guttata)